God, Gender, and Friendship: A Reading of Michelangelo’ s Pietà and Vittoria Colonna’ s Sonnet 87 - Gabrielli, Francesca Maria (2009)
The visual-verbal dialogue between Michelangelo’ s Pietà and Colonna’ s Sonnet 87 centers on a representation of the divine that, proceeding from the symmetrical and complementary relationship between Christ and the Virgin (perceived in their collaborative effort to redeem mankind), affects the asymmetrical stability of socially instituted gender categories and succeeds in bypassing gender hierarchy. If, on one hand, the Virgin is depicted in the drawing with the features of the biblical Rachel, opening up an intertextual field of woman-to- woman relations (Rachel and Leah), Christ is, on the other hand, represented in the sonnet as Procne. Needless to say, the identification of Jesus with Procne - apart from activating a doubling process that intertextually reformulates the former allusion to sister rivalry evoking sister solidarity (Procne and Philomela) - radically troubles accepted norms not only about the representation of the divine, but also about the masculine gender as such. Since “ to posit a gender, God is necessary” (Irigaray), such verbal/visual representation of the divine posits fluid and troubled gender categories.
Projekt MZOS
ENG